British Society of Gastroenterology/Association of Coloproctology of Great Britain and Ireland/Public Health England post-polypectomy and post-colorectal cancer resection surveillance guidelines. Issue 2 (27th November 2019) - Rutter, Matthew D; East, James; Rees, Colin J; Cripps, Neil; Docherty, James; Dolwani, Sunil; Kaye, Philip V; Monahan, Kevin J; Novelli, Marco R; Plumb, Andrew; Saunders, Brian P; Thomas-Gibson, Siwan; et al.
Abstract : These consensus guidelines were jointly commissioned by the British Society of Gastroenterology (BSG), the Association of Coloproctology of Great Britain and Ireland (ACPGBI) and Public Health England (PHE). They provide an evidence-based framework for the use of surveillance colonoscopy and non-colonoscopic colorectal imaging in people aged 18 years and over. They are the first guidelines that take into account the introduction of national bowel cancer screening. For the first time, they also incorporate surveillance of patients following resection of either adenomatous or serrated polyps and also post-colorectal cancer resection. They are primarily aimed at healthcare professionals, and aim to address: Which patients should commence surveillance post-polypectomy and post-cancer resection? What is the appropriate surveillance interval? When can surveillance be stopped? two or more premalignant polyps including at least one advanced colorectal polyp (defined as a serrated polyp of at least 10 mm in size or containing any grade of dysplasia, or an adenoma of at least 10 mm in size or containing high-grade dysplasia); or five or more premalignant polyps The Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument provided a methodological framework for the guidelines. The BSG's guideline development process was used, which is National Institute for Health and Care Excellence (NICE) compliant. two or more premalignant polyps including at least one advanced colorectal polyp (defined as a serrated polyp of at least 10 mm in size or containing any grade of dysplasia, or an adenoma of at least 10 mm in size or containing high-grade dysplasia); or five or more premalignant polyps The key recommendations are that the high-risk criteria for future colorectal cancer (CRC) following polypectomy comprise either : two or more premalignant polyps including at least one advanced colorectal polyp (defined as a serrated polyp of at least 10 mm in size or containing any grade of dysplasia, or an adenoma of at least 10 mm in size or containing high-grade dysplasia); or five or more premalignant polyps This cohort should undergo a one-off surveillance colonoscopy at 3 years. Post-CRC resection patients should undergo a 1 year clearance colonoscopy, then a surveillance colonoscopy after 3 more years.